THE BELIEF SYSTEM OF THE PEOPLE OF KAJANG: A PERSPECTIVE IN RELIGION ANTHROPOLOGY Sistem Kepercayaan orang Kajang dalam Perspektif Antropologi Agama - Basrah Gising (Al-Qalam, 2011)
Indigenous peoples of Kajang is an indigenous community that inhabit Kajang subsdistrict in Bulukumbaregency in South Sulawesi province. They adopt a belief system that called Jenne'Talluka'and SambajangTattappu. Jenne talluka means ablution water that never canceled, while sambajang tattappu meansalways remembering the God almighty oneKajang Indigenous peoples, especially those inhabited inside kajang (inside Embayya) still embrace andkeep up the belief system as mention above until now. Almost all of them do not carry out and shari'aandthe pillars of the Islam: uttering syahadat (confession) words, establishing prayer five times andthe Sunnah, fasting in Ramadan month, contribute to zakat, and fulfilling hajj worship.I use the Anthropology of Religion approach to study the belief system of such Kajang community.Through this approach, I will be focusing on a system of worship and religious behavior of Kajang indig-enous peoples.